Assessing the effect of sugar type and form of its intake on selected parameters of carbohydrate-lipid metabolism and plasma atherogenic indices in rats - Joanna Sadowska; Magda Bruszkowska (Roczniki Panstwowego Zakladu Higieny, 2019)
Background. Over the past 50 years, the average consumption of sugar worldwide has tripled, also the type of consumed sugar has changed. Due to high price of sucrose and its technological disadvantages, high fructose corn syrup (HFCS) has become one of the most commonly used substitutes. Objective. The aim of the study was to compare, on the animal model, the effect of sugar type (sucrose vs high fructose corn syrup 55% of fructose) and the sugar form (solid vs fluid and solid) on the chosen parameters of carbohydrate-lipid metabolism. Material and methods. The experiment was carried out on 40 Wistar male rats aged 5 months, fed four isocaloric diets, containing: group I (SUC 15%) fodder with 15% sucrose, group II (HFCS 15%) fodder with 15% HFCS-55%, group III (SUC 7.5%+7.5%) – 7.5% sucrose in solid fodder and 7.5% sucrose water solution, group IV (HFCS 7.5%+7.5%) – 7.5% HFCS-55% in solid fodder and 7.5% HFCS water solution. Results. The effect of HFCS-55 on the parameters of carbohydrate and lipid metabolism was not equivalent of the effect of sucrose. Dietary use of HFCS-55 instead of sucrose causes adverse changes in blood parameters of carbohydrate and lipid metabolism, particularly when provided in beverages, as at comparable weight gains to that of sucrose. More intense changes, manifesting in increased blood levels of glucose, triglycerides and uric acid, as well as increased liver fat content, were observed at simultaneous intake of sweeteners in solid foods and fluids, even with less sugar consumption, compared to solid food only. Conclusions. Dietary use of HFCS-55 causes adverse changes in blood parameters of carbohydrate and lipid metabolism, as at comparable weight gains to that of sucrose. But liquid form of sugar intake is more important insulin resistance and cardiovascular disease risk factor than the sugar type.